Genetic variability, heritability and genetic advance in F3 and F4 generations of the cross GKVK-4 × NRCG-12473 in groundnut: Genetic variability, heritability and genetic advance in F3 and F4 generations of the cross GKVK-4 × NRCG-12473 in groundnut - A VIJAYABHARATHI; D L SAVITHRAMMA (Journal of Oilseeds Research, 2020)
To study the quantum of variability for pod yield and water-use efficiency (WUE) related traits, F3 and F4 populations derived from the cross GKVK-4 × NRCG-12473 was evaluated. The variance indicated highly significant differences for all the ten characters studied. To conclude the present experimental results by considering variability and selection parameters simultaneously, specific leaf area @ 60 DAS and pod yield per plant exhibited high narrow sense heritability with high genetic advance as per cent of mean (GAM) implies that these characters have to be given more focus to improve the yield in groundnut breeding programme.